Feasibility, utility and symptom impact of modified mindfulness training in sarcoidosis. Issue 2 (8th May 2018) - Saketkoo, Lesley Ann; Karpinski, Aryn; Young, Jessica; Adell, Ryan; Walker, McCall; Hennebury, Tamarin; Wickremasinghe, Melissa; Russell, Anne-Marie
Sarcoidosis is a multisystem disorder characterised by noncaseating granulomatous inflammation of unknown aetiology. It may resolve spontaneously, but ∼30% of patients have progressive disease with significant organ damage [1]. Although any organ is vulnerable, the lungs are frequently involved resulting in shortness of breath and dry cough. Fatigue is an overarching symptom in sarcoidosis, originating from multiple and combined causes of mental fatigue and physical fatigue [2]. This is also true of the psychosocial impact of sarcoidosis, which may include depression, anxiety, isolation and feelings of uncertainty. The prevalence of these factors remains high even for those who achieve clinical remission, resulting in psychological distress and reduced health status [3]. A modified mindfulness-based exercise intervention has beneficial impact on people living with sarcoidosis http://ow.ly/XYTO30jtmms